Experience, challenges, and engagement amidst pandemic: The online learning to onsite learning - Friska Ria Sitorus; Pestaria Naibaho; Wolter Parlindungan Silalahi (Jurnal Penelitian Ilmu Pendidikan, 2023)
The Covid-19 pandemic has forced stakeholders to find the best way to carry out student learning activities through online learning as the best solution during the pandemic. However, the onsite learning system has been switching slowly in the last few months. The current study summarizes the narratives of the challenges and benefits of four undergraduates from the same major who joined online learning and onsite learning during the Covid-19 pandemic. Through a narrative qualitative, the lens examines the students' experiences. The instruments are interviews and diary notes of participants during conducting online and onsite learning amidst the pandemic and analyzed qualitatively. The findings showed that the students deal with four challenges: limited devices, lack of enthusiasm, anxiety, and unexpected disturbance during online learning. Meanwhile, the benefits save time, and cost, are easy to access, and students can learn independently. Moreover, this learning might help the student to become problem solvers and critical thinkers through task-solving activities and learning responsibilities. It also opens opportunities for students to better understand their own abilities in learning. Pengalaman, tantangan, dan keterlibatan di tengah pandemic: Pembelajaran online hingga pembelajaran luringPandemi Covid-19 memaksa para pemangku kepentingan untuk mencari cara terbaik dalam melaksanakan kegiatan belajar siswa melalui pembelajaran online sebagai solusi terbaik di masa pandemi. Namun, sistem pembelajaran di tatap muka telah beralih perlahan dalam beberapa bulan terakhir. Penelitian ini merangkum narasi perihal tantangan dan manfaat dari empat mahasiswa dari jurusan yang sama yang mengikuti pembelajaran online dan pembelajaran di tempat selama pandemi Covid-19. Instrumen yang digunakan berupa wawancara dan catatan harian peserta selama melakukan pembelajaran daring dan luring di tengah pandemi dan dianalisis secara kualitatif. Temuan menunjukkan bahwa siswa menghadapi empat tantangan: perangkat terbatas, kurangnya antusiasme, kecemasan, dan gangguan tak terduga selama pembelajaran online. Sedangkan keuntungannya adalah menghemat waktu, dan biaya, mudah diakses, dan siswa dapat belajar secara mandiri. Selain itu, pembelajaran ini dapat mendukung siswa untuk menjadi sosok pemecah masalah dan pemikir kritis melalui kegiatan pemecahan tugas dan tanggung jawab belajar. Hal ini juga membuka kesempatan bagi siswa untuk lebih memahami kemampuannya sendiri dalam belajar.